Effect of Different Types of Sugar and Fermentation Time on Total Alcohol Content of Eco Enzyme Based on Pineapple (Ananas comosus (L.) Merr)and Orange (Citrus x sinensis (L.) Osbeck) - Putri, Fitria; Setyowati, Erna; Pratiwi, Sylvia (Brawijaya University, 2026)
Introduction: Eco enzyme is a fermented product derived from a mixture of organic waste, sugar, and water (3:1:10). Fermented products produce alcohol (ethanol), which can be used as a reference for quality control, regulatory compliance, and biological activity. Several factors can affect alcohol content, including the type of sugar and fermentation time, both of which have not been widely researched. Objectives: This study aims to determine the effects of different types of sugar and fermentation time on the total alcohol content of eco-enzymes derived from pineapple and orange peels. Methods: The eco enzymes formed were evaluated organoleptically (color and aroma), pH, and total alcohol content were determined by the colorimetric method. Results: All samples changed color and aroma, formed sediment, and had a decrease in pH from a range of 5–6 to 3.44–4.22 after fermentation. The average total alcohol content obtained at fermentation after 30, 60, and 90 consecutive days was 2.336%, 3.072%, and 2.149%, respectively. The highest alcohol content was obtained in the 60-day fermentation molasses treatment of 3.512 ± 0.498%. Statistical analysis showed that fermentation time had a significant effect on the total alcohol content of eco enzymes (p < 0.001), whereas sugar type did not (p = 0.129). Conclusions: The results of this study show that fermentation time is an important factor in determining alcohol formation in the eco enzyme.